Understanding the nested, multi-scale, spatial and hierarchical nature of future climate change adaptation decision making in agricultural regions: A narrative literature review. (February 2015) - Lyle, Greg
Abstract: Historically, innovation in industrialised agricultural landscapes has been slow. Likewise, future climate change adaptation (CCA) will also be slow if complex interactions highlighted in the innovation and adoption literature are ignored. The aim of this review is to collate and conceptualise this multidisciplinary literature into a nested multi-scale spatial hierarchy to understand the complexity of the CCA decision making process, highlighting the influential factors across the nested scales. Seven nested hierarchical scales were identified under an overarching level of governance. The outer boundary is the Hazardscape – a spatially defined climatic region where potential impacts of climate change (CC) and suitable CCA strategies are defined. Differing socio-economic and demographic profiles ( Community Typologies ) under this scale mean that these strategies need to be tailored to enhance community adoption and bolster their resilience to CC. The strength and type of social interaction within and between Community will also influence CCA. Central to the hierarchy is the variation in Individuals ' beliefs and risk perceptions. Greater CC risk perception within the Household can enhance or constrain CCA at the Farm scale. In turn, the Farm scale attributes can influence CCA. Differing Farm and Farmer characteristics provide a further layer of complexity when considering CCA capability. Greater knowledge and evaluation of the circumstances and factors involved in CCA decision making highlighted by the use of the hierarchy will create an evidence base which will allow a more targeted approach to CCA. Adoption can be increased through a targeted range of CCA strategies and tailored plans of communication and dissemination of CC and CCA information across the nested scales. This approach will build much needed momentum for CCA in a rural setting. While the interaction between scales is discussed, future research is required to understand the cross-scale interactions, feedback loops and temporal dynamics within the hierarchy. Highlights: Innovation and climate change adaptation (CCA) in agricultural areas has been slow. A better understanding of the literature identified factors can help overcome this limitation. Factors can be placed into seven scales of a nested multi-scale spatial hierarchy. The hierarchy provides a further insight into this complex decision making environment. Greater understanding of the scales and interactions can increase future CCA adoption.